Long noncoding RNA TUG1 facilitates osteogenic differentiation of periodontal ligament stem cells via interacting with Lin28A - He, Qin (Cell Death Dis, 2018)
Periodontal ligament stem cells (PDLSCs) are mesenchymal stem cells derived from dental tissues with multidirectional differentiation potential and excellent self-renewing ability. Recently, long noncoding RNAs (lncRNAs) have been shown to play important roles in MSC osteogenic differentiation. In this study, we found that taurine upregulated gene 1 (TUG1), an evolutionarily conserved and widely present lncRNA was significantly upregulated in osteogenically induced PDLSCs compared to their undifferentiated counterparts. Further investigation demonstrated that the expression of TUG1 was positively correlated with the osteogenic differentiation of PDLSCs following the induction, as evidenced by the increase in cellular alkaline phosphatase (ALP) level, formation of calcium nodules, and the upregulation of several osteogenic-related gene markers such as ALP, osteocalcin (OCN), and runt-related transcription factor 2 (Runx2). Conversely, TUG1 knockdown was demonstrated to inhibit the potential of PDLSCs for osteogenic differentiation. Using bioinformatics analysis, we identified lin-28 homolog A (Lin28A) as a potential target of TUG1 during osteogenic differentiation of PDLSCs. Lin28A was found to be significantly downregulated in TUG1-repressed PDLSCs and contained multiple binding sites for lncRNA TUG1. Moreover, suppression of Lin28A was shown to be able to inhibit osteogenic differentiation and decreased the expression of several osteogenic genes. Taken together, these results could help researchers better understand the mechanism that governs the osteogenic differentiation of PDLSCs, and also serve as a stepping stone for the development of novel therapeutic strategies that can be used to regenerate dental tissues.